A Comparison between Primary and Secondary Flap Coverage in Ridge Preservation Procedures: A Pilot Randomized Controlled Clinical Trial. (20th August 2019) - Aladmawy, Majdi A.; Natto, Zuhair S.; Steffensen, Bjorn; Levi, Paul; Cheung, Wai; Finkelman, Matthew; Ogata, Yumi; Hur, Yong
Abstract : Aims . To assess the bone dimensional changes after extraction and alveolar ridge preservation (ARP) using primary coverage (closed flap technique, CFT) or healing by secondary intention (open flap technique, OFT). Materials and Methods . Ten patients (split mouth design) were planned for extraction and ARP. All sites received ARP with freeze-dried bone allograft (FDBA) and nonresorbable membrane after extraction. Clinical standardized measurements were used to assess the dimensional alterations of the alveolar ridge. Results . All patients completed the study, and a total of 20 sites were randomized to CFT or OFT group. Center height (mean difference of 8.1 mm, SD =1.9 CFT, and 7.5 mm, SD= 1.8 OFT) and buccal height (mean difference of 0.8 mm, SD =1.0 CFT, and 0.3 mm, SD= 1.1 OFT) were significantly different within the same group. However, there was no statistically significant difference between groups. In the OFT group, the keratinized tissue width was higher and the pain VAS scores at 24 hours were lower compared with the CFT ( p = 0.004 and p = 0.006, respectively). Conclusions . Leaving the flap open did not have any effects on the dimensional changes of bone height or width. However, there was a wider band of keratinized tissue and less pain with the CFT compared with the OFT. The study protocol was registered at ClinicalTrials.gov, IdentifierNCT03136913 .